2019
DOI: 10.1002/cctc.201801856
|View full text |Cite
|
Sign up to set email alerts
|

Thioesters as Acyl Donors in Biocatalytic Friedel‐Crafts‐type Acylation Catalyzed by Acyltransferase from Pseudomonas Protegens

Abstract: Functionalization of aromatic compounds by acylation has considerable significance in synthetic organic chemistry. As an alternative to chemical Friedel‐Crafts acylation, the C‐acyltransferase from Pseudomonas protegens has been found to catalyze C−C bond formation with non‐natural resorcinol substrates. Extending the scope of acyl donors, it is now shown that the enzyme is also able to catalyze C−S bond cleavage prior to C−C bond formation, thus aliphatic and aromatic thioesters can be used as acyl donors. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The substrate scope of Pp ATase has been investigated in recent studies, which demonstrated that this enzyme is capable of catalyzing the Friedel–Crafts acetylation of various resorcinol derivatives by using a wide range of acyl donors, such as acetate derivatives, phenyl esters, and thioesters. ,, Importantly, the acetylation is found to be highly chemo- and regioselective. No O -acetylated, polysubstituted, or hydrolyzed product was observed.…”
Section: Introductionmentioning
confidence: 99%
“…The substrate scope of Pp ATase has been investigated in recent studies, which demonstrated that this enzyme is capable of catalyzing the Friedel–Crafts acetylation of various resorcinol derivatives by using a wide range of acyl donors, such as acetate derivatives, phenyl esters, and thioesters. ,, Importantly, the acetylation is found to be highly chemo- and regioselective. No O -acetylated, polysubstituted, or hydrolyzed product was observed.…”
Section: Introductionmentioning
confidence: 99%
“…In Scheme a, the important features of an enzyme contributing to the different steps are exemplified for an enzyme enabling a C–C bond formation, namely, the acylation of resorcinol. The natural reaction of this acyltransferase is the disproportionation of monoacetyl-phloroglucinol (Scheme b); , however, it turned out that the natural catalyst shows promiscuous activity to also accept esters (e.g., phenyl or vinyl) as acyl donors and to link the acyl group to (substituted) resorcinol via the formation of a new C–C bond. This is remarkable because O -acylation occurs under chemical catalysis.…”
Section: High-tech Features Of a Biocatalystmentioning
confidence: 99%
“…Remarkably, for o-acyl derivatives, a rearrangement leading to the c-acylated product was observed in the presence of the ATase, which represents a formal Fries reaction and the first biocatalytic example. The influence of different additives [25] and acyl donors [26] was also studied and will inspire future research in this area that will enable the development of greener alternatives to this relevant reaction.…”
Section: Biocatalytic Friedel-crafts and Fries Reactionsmentioning
confidence: 99%